"You have to be okay with okay": experiences of flourishing among university students transitioning directly from high school. Issue 1 (1st January 2020) - Volstad, Christina; Hughes, Jean; Jakubec, Sonya L.; Flessati, Sonya; Jackson, Lois; Martin-Misener, Ruth
ABSTRACT: Mental health is central to overall wellbeing and, for students attending university, mental health is critical for learning and academic success. A wealth of research has focused on young people who experience psychosocial declines during academic and developmental transitions, but little is known about how young people flourish in this transition. The first to explore the experiences of flourishing among first-year Canadian university students making the transition directly from high school, this study sought to develop an understanding of: 1) the factors that promote flourishing amidst this academic and developmental transition, and 2) how first-year students define and experience flourishing . An interpretive phenomenological approach underpinned by Gadamerian hermeneutic philosophy was used to explore experiences of flourishing, using semi-structured interviews, in a sample of nine full-time, first-year university students, ages 18–20 years. What it meant to flourish amidst this developmental and academic transition and how participants defined flourishing offer new understandings of the concept associated with: 1) personal/individual aspects of flourishing, 2) contextual nature of flourishing, 3) temporality of flourishing, 4) dialectic aspects of flourishing . Implications for practice, policy, and research in light of these new understandings are discussed.